Balancing inclusion and exclusion among Somali migrants in Germany - Markus Virgil Hoehne; Tabea Scharrer (International Migration, 2023)
We discuss the balancing acts of inclusion and exclusion by analysing how Somali migrants in Germany attempt to manoeuvre between various norms, individual interests and various social networks. Building on Glick Schiller and Caglar (2016), whose work on urban sociabilities emphasizes social relations in which people act as equals, we argue that ethnic (self-)identification is important as it serves as a basis for boundary-making and for bonding within and bridging and linking between groups. Thus, a focus on sociability and ethnic identification (as a category of praxis) can, in some cases, go hand in hand. Moreover, we argue that inclusion into local Somali communities, which is often discussed in public discourse as leading to exclusion from German society, helps to establish connections. Simultaneously, exclusion through racism can lead to (self-)isolation of Somalis, but also places pressure on younger Somalis in particular to forge alliances with non-Somali Germans to stabilize their situation. Balancing social inclusion and exclusion among Somali migrants in Germany therefore can have ambiguous and at times paradoxical outcomes.
Keywords: 300